2010
DOI: 10.1002/cncr.25728
|View full text |Cite
|
Sign up to set email alerts
|

Late age at first full term birth is strongly associated with lobular breast cancer

Abstract: BACKGROUND: Late age at first full-term birth and nulliparity are known to increase breast cancer risk. The frequency of these risk factors has increased in recent decades. METHODS: The purpose of this population-based casecontrol study was to examine associations between parity, age at first birth (AFB), and specific histological subtypes of breast cancer. Women with breast cancer were identified from cancer registries in Wisconsin, Massachusetts, and New Hampshire. Control subjects were randomly selected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 63 publications
3
27
0
Order By: Relevance
“…The CBCS is a population based case-control study that was carried out in Wisconsin, Massachusetts (apart from metropolitan Boston), Maine and New Hampshire (1618). Eligible case subjects were women identified by each state’s cancer registry with a new breast cancer diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The CBCS is a population based case-control study that was carried out in Wisconsin, Massachusetts (apart from metropolitan Boston), Maine and New Hampshire (1618). Eligible case subjects were women identified by each state’s cancer registry with a new breast cancer diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis of 9 cohort or case–control studies also revealed a reduced risk among patients with hormone receptor-positive cancers [17]. This protective effect was also observed in lobular carcinomas that are often positive for hormone receptors [25]. In this context, the relative protective effect of young age of first full-term birth has been observed mainly for postmenopausal women [17, 23, 24, 26].…”
Section: Age Of First Full-term Birthmentioning
confidence: 99%
“…Nulliparity may be associated with ovulatory disorders in the majority of cases and there are studies, which equivocally exhibited increased prevalence of breast cancer in nulliparous women [161, 162]. Furthermore, coexistence of nulliparity and overweight may amplify each other’s effect on increasing breast cancer risk having strong synergism [161].…”
Section: Introductionmentioning
confidence: 99%